2011
DOI: 10.2967/jnumed.111.092965
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Radionuclides for Optical Imaging: Cerenkov Luminescence Imaging

Abstract: Over the past several years, nuclear imaging modalities such as PET and SPECT have received much attention because they have been instrumental not only in preclinical cancer research but also in nuclear medicine. Yet nuclear imaging is limited by high instrumentation cost and subsequently low availability to basic researchers. Cerenkov radiation, a relativistic physical phenomenon that was discovered 70 years ago, has recently become an intriguing subject of study in molecular imaging because of its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 33 publications
5
180
0
Order By: Relevance
“…Recently, Thorek et al demonstrated that significantly high sensitivity could be achieved with CLI as low amounts of 18 F-FDG accumulated (about 2Ci) in the nodes of patients 39,40 . In vitro testing indicated that CLI signal from 0.01 Ci 90Y was detectable in solution 25,32,33 . Moreover, CLI also has the potential for high spatial resolution and the capacity for high throughput screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Thorek et al demonstrated that significantly high sensitivity could be achieved with CLI as low amounts of 18 F-FDG accumulated (about 2Ci) in the nodes of patients 39,40 . In vitro testing indicated that CLI signal from 0.01 Ci 90Y was detectable in solution 25,32,33 . Moreover, CLI also has the potential for high spatial resolution and the capacity for high throughput screening.…”
Section: Discussionmentioning
confidence: 99%
“…In this protocol, we demonstrate that CLI with 18 F-FDG can be applied for optically imaging BAT in small animals. Like other optical imaging techniques, tissue penetrating limitation and low sensitivity for deep targets are the intrinsic limitations of CLI 25,32 . 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…); (2) Understanding the advantages and limitations of different molecular platforms for clinical translation, establish new chemistry for probe synthesis and preparation, keep testing novel strategies for design new generation of probes, incorporate signal amplification, and targeted imaging mechanisms into the probe, develop generalizable approach for facilitating probe translation, and combine imaging and therapy together; (3) Exploring the potential use of multimodality imaging, examine the necessity of combining different imaging modalities for different medical scenarios, supply well-designed and rationalized multimodality imaging probes to the research community; (4) Realize multiplex imaging ability through novel imaging modalities and probes, integrate in vitro diagnosis and pathology and in vivo molecular imaging to achieve best diagnosis and management of diseases; (5) Develop new imaging modalities or hybrid imaging modalities as mentioned above. Besides the conventional imaging modalities (MRI, CT, PET, SPECT, optical imaging), novel single or hybrid imaging modalities such as Raman imaging, Cerenkov luminescence imaging, X-ray excited luminescence imaging, or X-ray excited acoustic imaging could surpass many traditional imaging modalities and provide new information on diseases and complex mechanisms (Keren et al, 2008;Sun et al, 2011;Xu et al, 2011;Xiang et al, 2013).…”
Section: Molecular Imagingmentioning
confidence: 99%
“…18 In this regard, Cerenkov luminescence imaging (CLI) is a promising optical-based method based on the unique property of photo-emission from luminescent radionuclides when the charged particles (mostly β + ) travel through water with velocities faster than the speed of light. 18,19 In spite of many attempts to use PET radionuclides, such as 64 Cu, 68 Ga and 124 I for CLI-based optical imaging, 20 the quantitative relationship between PET and CLI imaging has not yet been firmly established, though such knowledge is required for future CLI-based imaging in clinical applications.…”
Section: Introductionmentioning
confidence: 99%